Aspectos desafiadores da relação terapêutica com adolescentes e suas oportunidades de intervenção: uma teoria fundamentada em dados - Pereira, Samanta Alves (2025)
Adolescence is a transitional period characterized by profound biological, psychological, and social transformations, which impact both the individual and their environment. This context also influences the clinical process, presenting inherent challenges in therapeutic work with adolescents, such as low adherence to treatment, the tendency to generalize the therapist as an authority figure, the impact of generational differences, and the need for family involvement in the process. This study, based on the principles of Grounded Theory, developed a theoretical model from 20 interviews with behavioral therapists. This model describes the challenges therapists face when working with adolescents and provides insights into how these difficulties can be transformed into therapeutic opportunities and strategic possibilities in clinical practice with this population. The study highlights the significance of the therapeutic relationship for the success of therapy: establishing a transparent and trusting environment is essential so that the therapist does not assume a role similar to other authority figures in the adolescent’s life. The therapist must adopt an active stance, engaging in self-reflection regarding the emotional impact that the client may have on them. This study outlines the difficulties inherent in this process and demonstrates that there are ways to address these issues, which can also serve as opportunities for professional growth. The outcome of this research is an intermediate-level theoretical model that functions as a descriptive roadmap for a possible theoretical and practical approach to adolescent therapy. For educational purposes, its implications have been compiled into a guide that makes theory and practice easily accessible to therapists